Patients' Attitudes Toward Electronic Health Information Exchange: Qualitative Study - Simon, Steven R; Evans, J Stewart; Benjamin, Alison; Delano, David; Bates, David W (JMIR Publications, 2009)
Background In many countries, there has been substantial progress in establishing the electronic transmission of patients' health information between health care providers, but little is known about how best to engage patients in the process. ObjectiveWe explored patients' views about sharing of electronic health information and their preferences for learning about and participating in this process. MethodsPatients in one Massachusetts community in the northeastern United States were recruited to participate in focus-group discussions. Prior to discussion, participants completed a written questionnaire that captured their reactions to draft educational materials and a consent form. The discussion moderator and two physicians analyzed the moderator's detailed notes from each session and participants' written comments, using an immersion-crystallization approach. ResultsThree dominant themes emerged: (1) concerns about privacy and security, (2) the potential benefit to a person's health, and (3) the desire for more information about the consent process. On the pre-discussion questionnaire, 55 out of 62 participants (88%) indicated that they would provide consent for their information to be shared electronically among their health care providers, given the materials they had reviewed. ConclusionsPatients are enthusiastic about electronic health information exchange, recognizing its capacity to improve the quality and safety of health care; however, they are also concerned about its potential to result in breached privacy and misuse of health data. As the exchange of electronic health information becomes more widespread, policy makers will need to ensure that patients have access to concise educational materials and opportunities to engage in conversations about the risks and benefits of participation.